Metal Ion Reduction, Chelation, and Cytotoxicity of Selected Bicyclic Monoterpenes and Their Binary Mixtures - Karolina Wojtunik-Kulesza; Marcela Dubiel; Katarzyna Klimek (Metabolites)
Background/Objectives: Bicyclic monoterpenes are one of the most common groups of secondary plant metabolites found in Nature. Their wide spectrum of biological activity can be used in the prevention and in the treatment of various diseases, including so-called ‘diseases of civilization’. Their potential for synergistic interactions may influence the biological activities of more complex mixtures. Methods: This study investigated the ability of selected bicyclic monoterpenes and their binary mixtures to reduce Fe(III) and Cu(II) and chelate Fe(II) and assessed their cytotoxic activity against BJ and HepG2 cell lines. Results: The obtained results did not reveal synergistic interactions towards the biological activities, but binary mixtures proved to be safe in relation to the tested cell lines. Among the tested single monoterpenes, the most effective were 3-carene and β-pinene, with the latter exhibiting the greatest ability to decrease cell viability (CC50 for BJ and HepG2 cells was about 1.08 and 1.85 mM, respectively). Conclusions: The results revealed that both single compounds and binary mixtures demonstrate the ability to reduce selected metal ions and chelate Fe(II) ions. Synergistic interactions were not observed, but an increase in the activity of selected binary mixtures was recorded. Based on cell culture experiments, the monoterpenes and their binary mixtures can be considered safe at a concentration lower than 1 mM and close to 0.313 mM, respectively.